Sacred seeds: new world plants in early modern English literature - Test, Edward McLean (Early Modern Cultural Studies, 2019)
Cover -- Title Page -- Copyright Page -- Contents -- List of Illustrations -- Acknowledgments -- Introduction -- 1. New Seeds, Strange Countries -- 2. People of the Figs -- 3. King Tobacco -- 4. The Holy Wood of America -- 5. Love Lies Bleeding -- Epilogue -- Notes -- Bibliography -- Index.